Liquid phase growth carbon nanotube modified CMC-SiC composite material and preparation method thereof

By using liquid-phase-grown carbon nanotube modification technology in CMC-SiC composites, and using vacuum impregnation and catalytic cracking methods to grow carbon nanotubes in situ in CMC-SiC composites, the preparation process in the prior art is not easy to control. The problem of this has achieved the improvement of high performance and thermal conductivity of CMC-SiC composite materials.

CN119191859APending Publication Date: 2024-12-27SDIC CERAMIC MATRIX COMPOSITES RES INST (XIAN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411201791.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing preparation methods of CNTs modified materials are not suitable for use in CMC-SiC composites, and the preparation process is not easy to control and is not suitable for large-sized composites.

Method used

CMC-SiC composites modified with liquid-phase growth carbon nanotubes were grown in situ on the neutral surface of the CMC-SiC composite body by vacuum impregnation and catalytic cracking. Carbon nanotubes were grown in situ on the body of the CMC-SiC composite material, and carbon nanotubes were performed using phenolic resin and catalyst. Even growth of the tube.

Benefits of technology

The good mechanical properties and high temperature resistance of CMC-SiC composite materials are achieved, the preparation process is simplified, the cost is reduced, and it is suitable for large-size composite materials, and the thermal conductivity is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191859A_ABST
    Figure CN119191859A_ABST
Patent Text Reader

Abstract

The invention provides a liquid-phase growth carbon nanotube modified CMC-SiC composite material and a preparation method thereof, and can solve the problems that the existing preparation method of a CNTs modified material is not suitable for being applied to the CMC-SiC composite material, and most methods are not easy to control the preparation process and are not suitable for a large-size composite material. The preparation method of the composite material comprises the following steps: preparing a phenolic resin solution with the mass fraction of 5-50%; weighing a catalyst of which the mass is 1-10% of that of the phenolic resin powder, adding the catalyst into the phenolic resin solution, performing ultrasonic dispersion for at least 10 minutes, and continuously stirring for at least 2 hours until the catalyst is completely dissolved to obtain a mixed solution; immersing a pre-prepared CMC-SiC composite material body into the mixed solution, and carrying out vacuum impregnation for at least 10 minutes; and taking out the CMC-SiC composite material body after vacuum impregnation, placing the CMC-SiC composite material body in a heating container, then placing the CMC-SiC composite material body in a tubular furnace, introducing argon, and carrying out heat treatment at a heating temperature of 800-1200 DEG C for at least 1 h to obtain the liquid-phase growth carbon nanotube modified CMC-SiC composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified continuous fiber toughened SiC ceramic matrix composite material (CMC-SiC), in particular to a liquid phase grown carbon nanotube modified CMC-SiC composite material and a preparation method thereof. Background Art

[0002] Continuous fiber reinforced silicon carbide ceramic matrix composite (CMC-SiC) combines the advantages of C / C composites and SiC ceramics, and can meet the requirements of long-term use in an aerobic environment below 1650°C, limited life below 2000°C, and instantaneous life below 2800°C. CMC-SiC composites have a series of excellent properties such as high specific strength, high specific mass, ablation resistance, high temperature resistance, and low density. It is one of the most promising thermal protection system materials. With the implementation of aerospace science and technology projects, higher and more stringent technical requirements have been put forward for thermal protection system materials.

[0003] In order to further improve the performance of CMC-SiC thermal protection system materials and meet the harsh service environment of hypersonic aircraft, CMC-SiC composite materials are usually modified and other phases are introduced into CMC-SiC composite materials. However, this method has a certain upper limit on the high temperature resistance of the material itself. Therefore, non-ablative thermal protection materials have gradually become a research hotspot in the field of ultra-high temperature resistance. Non-ablative thermal protection materials are also called reusable thermal protection system materials. The main difference from ablative thermal protection materials is that under long-term aerodynamic heating conditions, the surface of non-ablative thermal protection materials will not be significantly ablated, and the shape of the aircraft can be kept basically unchanged. When external heat reaches the surface of the material, most of the heat is radiated from the surface through thermal radiation and convection heat transfer, and only a small amount of heat is conducted into the material.

[0004] Carbon nanotubes have excellent mechanical properties and unique electrical properties. At the same time, they also have good high temperature resistance and are a good thermal conductor. Therefore, carbon nanotubes are usually used to modify materials to obtain non-ablative thermal protection materials. Su et al. modified phenolic resin with carbon nanotubes and studied the preparation method of carbon nanotube-modified phenolic resin. The study showed that carbon nanotubes can significantly improve the heat resistance of phenolic resin (see: Research on carbon nanotube-modified phenolic resin, Carbon Technology, Vol. 118, No. 1, 2002). Wei et al. modified phenolic resin with carbon nanotubes and studied the effect of carbon nanotube (CNTs) content on the mechanical properties of PF / carbon fiber (CF) composite materials. The study showed that CNTs can significantly improve the mechanical properties of PF / CF composite materials (see: Effect of carbon nanotubes on the mechanical properties of phenolic resin / carbon fiber composite materials, Engineering Plastics Application, Vol. 34, No. 6, 2006). Vinod P in situ grows oriented CNTs on the surface of SiC fiber, and then impregnates high temperature resistant epoxy resin to obtain a resin-based composite material with a "sandwich" structure. After the introduction of oriented CNTs, the flexural strength and fracture toughness of the composite material increased by 140% and 424% respectively, and the thermal conductivity increased by 51.5% (see: Multifunctional composites using reinforced laminae with carbon-nanotube forests, Nature Materials, Vol. 5, No. 6, May 7, 2006). At present, there are relatively few studies and reports on CNTs modified CMC-SiC composite materials, and the preparation methods of the above-mentioned CNTs modified materials reported are not suitable for application in CMC-SiC composite materials, and most methods have problems such as difficult control of the preparation process and are not suitable for large-size composite materials. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problems that the existing preparation methods of CNTs modified materials are not suitable for application in CMC-SiC composite materials, and most methods have the problem that the preparation process is difficult to control and is not suitable for large-size composite materials, and to provide a liquid phase grown carbon nanotube modified CMC-SiC composite material and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A liquid phase grown carbon nanotube modified CMC-SiC composite material, which is special in that:

[0008] The invention comprises a CMC-SiC composite body and carbon nanotubes in-situ grown in the body and on the surface of the CMC-SiC composite body.

[0009] Furthermore, the carbon nanotubes are grown in situ in the CMC-SiC composite material body and on its surface using liquid phenolic resin as the main raw material through a vacuum impregnation method combined with a catalytic cracking method.

[0010] At the same time, the present invention also provides a method for preparing the above-mentioned liquid phase grown carbon nanotube modified CMC-SiC composite material, which is special in that it comprises the following steps:

[0011] Step 1, weighing phenolic resin powder and an organic solvent respectively, placing them in a container and stirring them until the phenolic resin powder is completely dissolved and the solution is clear and transparent, thereby preparing a phenolic resin solution with a mass fraction of 5% to 50%;

[0012] Step 2, weighing a catalyst with a mass of 1% to 10% of the mass of the phenolic resin powder, and adding it to the phenolic resin solution, after ultrasonic dispersion for at least 10 minutes, continuously stirring for at least 2 hours until the catalyst is completely dissolved to obtain a mixed solution; the catalyst is used to catalyze the growth of carbon nanotubes;

[0013] Step 3, immersing the pre-prepared CMC-SiC composite material body in the mixed solution, and vacuum impregnating for at least 10 minutes;

[0014] Step 4: Take out the CMC-SiC composite material body after vacuum impregnation and place it in a heating container, then put it into a tubular furnace, pass argon gas, and heat treat it at a heating temperature of 800°C to 1200°C for at least 1 hour to obtain a CMC-SiC composite material modified by liquid phase growth carbon nanotubes.

[0015] Furthermore, in step 1, the organic solvent is anhydrous ethanol or acetone; and the mass fraction of the phenolic resin solution is 10% to 30%.

[0016] Furthermore, in step 2, the mass of the catalyst is 3% to 8% of the mass of the phenolic resin powder; the catalyst is nickelocene or ferrocene; the ultrasonic dispersion time is 10 min to 50 min; and the stirring time is 2 h to 6 h.

[0017] Furthermore, in step 3, the CMC-SiC composite material body is a carbon cloth or a preform on which SiC is deposited; the vacuum impregnation time is 10 min to 60 min;

[0018] In step 4, the heat treatment time is 1 h to 4 h.

[0019] The above-mentioned organic solvent is selected from anhydrous ethanol or acetone, which has low cost; by further adjusting the mass fraction of the phenolic resin, the mass of the catalyst and the conditions of the subsequent heat treatment, the distribution of the catalyst can be more effectively regulated, which is more conducive to achieving uniform growth of carbon nanotubes in the CMC-SiC composite body and on its surface.

[0020] Furthermore, in step 3, the preform is a carbon fiber preform or a SiC fiber preform; and the structure of the preform is a two-dimensional laminate, a three-dimensional needle punching or a three-dimensional woven structure.

[0021] Furthermore, step 1 is specifically as follows:

[0022] Phenolic resin powder and anhydrous ethanol were weighed separately and placed in a container for stirring until the phenolic resin powder was completely dissolved and the solution was clear and transparent, thereby preparing a phenolic resin solution with a mass fraction of 15%.

[0023] Furthermore, step 2 is specifically as follows:

[0024] Weigh 5% of the mass of the phenolic resin powder with nickelocene, add it into the phenolic resin solution, disperse it by ultrasonic for 30 minutes, and continue stirring for 3 hours until the nickelocene is completely dissolved to obtain a mixed solution.

[0025] Furthermore, step 3 specifically comprises immersing the pre-prepared carbon fiber preform with a three-dimensional woven structure in the mixed liquid and vacuum impregnating it for 30 minutes;

[0026] Step 4 is specifically to take out the carbon fiber preform after vacuum impregnation and place it in a crucible, then put it into a tubular furnace, pass argon gas, and heat treat it at a heating temperature of 1000°C for 1.5 hours to obtain a carbon fiber preform modified by liquid phase growth carbon nanotubes.

[0027] Beneficial effects of the present invention:

[0028] 1. The present invention provides a liquid phase grown carbon nanotube modified CMC-SiC composite material and a preparation method thereof, wherein, since the carbon nanotubes are in-situ grown in the CMC-SiC composite material body and on its surface, the composite material has good mechanical properties and high temperature resistance, and its service life can be extended. The preparation process of the present invention is simple, low in cost, and the preparation process is easy to control, and is suitable for large-size composite materials.

[0029] 2. This method can effectively regulate the distribution of the catalyst by adjusting the mass fraction of the phenolic resin, the mass of the catalyst, and the temperature of the subsequent heat treatment, so as to achieve uniform growth of carbon nanotubes in the CMC-SiC composite body and on its surface. The present invention has low requirements on equipment and processing conditions, can effectively utilize the cracking products of the phenolic resin to grow carbon nanotubes in the CMC-SiC composite body and on its surface, and the preparation process uses normal pressure equipment. This method is safer and more reliable than chemical vapor deposition.

[0030] 3. The present invention realizes the combination of carbon nanotubes and CMC-SiC composite body by vacuum impregnation method and catalytic cracking method. This method does not depend on the configuration of the preform, which is conducive to engineering and industrial production. In addition, phenolic resin powder has low cost and wide source, which is of great significance for realizing the controllable macro-preparation of carbon nanotubes in CMC-SiC composite body.

[0031] 4. This method solves the problem that fibers cannot toughen CMC-SiC composites at the submicron scale, improves the thermal conductivity of the composite material, and constructs a heat conduction channel from the fiber to the matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a roadmap of the preparation method of the liquid phase grown carbon nanotube modified CMC-SiC composite material of the present invention;

[0033] Figure 2 1 is a SEM image of a carbon fiber preform modified by liquid phase grown carbon nanotubes in Example 1 of the present invention; wherein (a) and (b) are SEM images of a carbon fiber preform modified by liquid phase grown carbon nanotubes at different magnifications;

[0034] Figure 3 This is a diagram showing the diameter distribution of carbon nanotubes on the carbon fiber preform in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] Embodiment 1

[0036] A liquid phase grown carbon nanotube modified CMC-SiC composite material comprises a CMC-SiC composite material body and carbon nanotubes, wherein the carbon nanotubes are grown in situ in the CMC-SiC composite material body and on its surface by using a liquid phase phenolic resin as the main raw material through a vacuum impregnation method combined with a catalytic cracking method. In this embodiment, the carbon nanotubes are grown in and on the surface of a carbon fiber preform with a three-dimensional woven structure.

[0037] like Figure 1 As shown, a method for preparing a liquid phase grown carbon nanotube modified CMC-SiC composite material comprises the following steps:

[0038] Step 1: Weigh 45 g of phenolic resin powder and 255 g of anhydrous ethanol respectively, place them in a beaker and stir until the phenolic resin powder is completely dissolved and the solution is clear and transparent, to prepare 300 g of phenolic resin solution with a mass fraction of 15%.

[0039] Step 2: Weigh 2.25 g nickelocene (5% of the mass of the phenolic resin powder) and add it to the phenolic resin solution prepared in step 1. After ultrasonic dispersion for 30 min, continue stirring for 3 h until the nickelocene is completely dissolved to obtain a mixed solution.

[0040] Step 3: immerse the pre-prepared carbon fiber preform with a three-dimensional woven structure in the mixed solution obtained in step 2, and vacuum impregnate for 30 minutes.

[0041] Step 4: Take out the carbon fiber preform after vacuum impregnation in step 3 and place it in a crucible, then put it into a tube furnace, exhaust the air with argon, and heat treat it at a heating temperature of 1000°C for 1.5h to obtain a carbon fiber preform modified by liquid phase growth carbon nanotubes, the specific morphology of which is as follows: Figure 2 As shown. Figure 2 It can be seen that the carbon nanotubes grow uniformly inside and on the surface of the carbon fiber preform, and the length of the grown carbon nanotubes is about 3 μm. Figure 3 : is a diameter distribution diagram of carbon nanotubes on a carbon fiber preform. It can be seen from the figure that the diameter of the carbon nanotubes grown in the liquid phase on the carbon fiber preform is about 80nm.

[0042] Embodiment 2

[0043] The difference between this embodiment and the first embodiment is that the carbon nanotubes are grown inside and on the surface of the carbon cloth on which SiC is deposited.

[0044] The preparation method of this embodiment comprises the following steps:

[0045] Step 1, weigh 40g of phenolic resin powder and 360g of anhydrous ethanol respectively, and place them in a beaker for stirring until the phenolic resin powder is completely dissolved and the solution is clear and transparent, to prepare 400g of phenolic resin solution with a mass fraction of 10%.

[0046] Step 2: Weigh 3.2 g of ferrocene (8% of the mass of the phenolic resin powder) and add it to the phenolic resin solution prepared in step 1. After ultrasonic dispersion for 40 min, continue stirring for 4 h until the ferrocene is completely dissolved to obtain a mixed solution.

[0047] Step 3: Immerse the pre-prepared carbon cloth with SiC deposited thereon in the mixed solution obtained in step 2, and vacuum impregnate for 40 minutes.

[0048] Step 4: Take out the carbon cloth after vacuum impregnation in step 3 and place it in a crucible, then put it into a tube furnace, exhaust the air with argon gas, and heat treat it at a heating temperature of 1100°C for 1h to obtain a carbon cloth modified by liquid phase growth carbon nanotubes and deposited with SiC. The specific morphology is shown in Figure 2 . Diameter distribution of carbon nanotubes on carbon cloth deposited with SiC Figure 3 .

[0049] Embodiment 3

[0050] The difference between this embodiment and the first embodiment is that the carbon nanotubes are grown in and on the surface of the SiC fiber preform with a three-dimensional needle-punched structure.

[0051] The preparation method of this embodiment comprises the following steps:

[0052] Step 1: Weigh 150 g of phenolic resin powder and 350 g of acetone respectively, place them in a beaker and stir until the phenolic resin powder is completely dissolved and the solution is clear and transparent, to prepare 500 g of phenolic resin solution with a mass fraction of 30%.

[0053] Step 2: Weigh 15 g of ferrocene (10% of the mass of the phenolic resin powder) and add it to the phenolic resin solution prepared in step 1. After ultrasonic dispersion for 50 min, continue stirring for 6 h until the ferrocene is completely dissolved to obtain a mixed solution.

[0054] Step 3: immerse the pre-prepared SiC fiber preform with a three-dimensional needle-punched structure in the mixed solution obtained in step 2, and vacuum impregnate for 50 minutes.

[0055] Step 4: Take out the SiC fiber preform after vacuum impregnation in step 3 and place it in a crucible, then put it into a tube furnace, exhaust the air with argon, and heat treat it at a heating temperature of 1200°C for 1h to obtain a SiC fiber preform modified by liquid phase growth carbon nanotubes. The specific morphology is shown in Figure 2 . The diameter distribution of carbon nanotubes on SiC fiber preforms is shown in Figure 2. Figure 3 .

[0056] Embodiment 4

[0057] The difference between this embodiment and the first embodiment is that the carbon nanotubes are grown in and on the surface of the carbon fiber preform with a two-dimensional laminated structure.

[0058] The preparation method of this embodiment comprises the following steps:

[0059] Step 1: Weigh 100 g of phenolic resin powder and 100 g of anhydrous ethanol respectively, place them in a beaker and stir until the phenolic resin powder is completely dissolved and the solution is clear and transparent, thereby preparing 200 g of a phenolic resin solution with a mass fraction of 50%.

[0060] Step 2: Weigh 3 g of nickelocene (3% of the mass of the phenolic resin powder) and add it to the phenolic resin solution prepared in step 1. After ultrasonic dispersion for 10 min, continue stirring for 5 h until the nickelocene is completely dissolved to obtain a mixed solution.

[0061] Step 3: immerse the pre-prepared carbon fiber preform with a two-dimensional laminated structure in the mixed solution obtained in step 2 and vacuum impregnate for 60 minutes.

[0062] Step 4: Take out the carbon fiber preform after vacuum impregnation in step 3 and place it in a crucible, then put it into a tube furnace, exhaust the air with argon, and heat treat it at a heating temperature of 800°C for 4 hours to obtain a carbon fiber preform modified by liquid phase growth carbon nanotubes. The specific morphology is shown in Figure 2 . The diameter distribution of carbon nanotubes on carbon fiber preforms is shown in Figure 2. Figure 3 .

[0063] Embodiment 5

[0064] The difference between the preparation method of this embodiment and the preparation method of embodiment 2 is:

[0065] Step 1: Weigh 5 g of phenolic resin powder and 95 g of acetone respectively, place them in a beaker and stir until the phenolic resin powder is completely dissolved and the solution is clear and transparent, to prepare 100 g of a phenolic resin solution with a mass fraction of 5%.

[0066] Step 2: Weigh 0.05 g of ferrocene (1% of the mass of the phenolic resin powder) and add it to the phenolic resin solution prepared in step 1. After ultrasonic dispersion for 30 minutes, continue stirring for 2 hours until the ferrocene is completely dissolved to obtain a mixed solution.

[0067] Step 3: Immerse the pre-prepared carbon cloth with SiC deposited thereon in the mixed solution obtained in step 2, and vacuum impregnate for 10 minutes.

[0068] Step 4: Take out the carbon cloth after vacuum impregnation in step 3 and place it in a crucible, then put it into a tube furnace, exhaust the air with argon gas, and heat treat it at a heating temperature of 1100°C for 1h to obtain a carbon cloth modified by liquid phase growth carbon nanotubes and deposited with SiC. The specific morphology is shown in Figure 2 . Diameter distribution of carbon nanotubes on carbon cloth deposited with SiC Figure 3 .

[0069] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A CMC-SiC composite material modified by liquid phase grown carbon nanotubes, characterized in that: The invention comprises a CMC-SiC composite body and carbon nanotubes in-situ grown in the body and on the surface of the CMC-SiC composite body.

2. The CMC-SiC composite material modified by liquid phase grown carbon nanotubes according to claim 1, characterized in that: The carbon nanotubes are mainly made of liquid phenolic resin and are in-situ grown in and on the surface of the CMC-SiC composite material body by a vacuum impregnation method combined with a catalytic cracking method.

3. A method for preparing the CMC-SiC composite material modified by liquid phase growth carbon nanotubes according to claim 1 or 2, characterized in that: The following steps are involved: Step 1, weighing phenolic resin powder and an organic solvent respectively, placing them in a container and stirring them until the phenolic resin powder is completely dissolved and the solution is clear and transparent, thereby preparing a phenolic resin solution with a mass fraction of 5% to 50%; Step 2, weighing a catalyst with a mass of 1% to 10% of the mass of the phenolic resin powder, and adding it to the phenolic resin solution, after ultrasonic dispersion for at least 10 minutes, continuously stirring for at least 2 hours until the catalyst is completely dissolved to obtain a mixed solution; the catalyst is used to catalyze the growth of carbon nanotubes; Step 3, immersing the pre-prepared CMC-SiC composite material body in the mixed solution, and vacuum impregnating for at least 10 minutes; Step 4: Take out the CMC-SiC composite material body after vacuum impregnation and place it in a heating container, then put it into a tubular furnace, pass argon gas, and heat treat it at a heating temperature of 800°C to 1200°C for at least 1 hour to obtain a CMC-SiC composite material modified by liquid phase growth carbon nanotubes.

4. The method for preparing the CMC-SiC composite material modified by liquid phase growth carbon nanotubes according to claim 3, characterized in that: In step 1, the organic solvent is anhydrous ethanol or acetone; the mass fraction of the phenolic resin solution is 10% to 30%.

5. The method for preparing the CMC-SiC composite material modified by liquid phase growth carbon nanotubes according to claim 3 or 4, characterized in that: In step 2, the mass of the catalyst is 3% to 8% of the mass of the phenolic resin powder; the catalyst is nickelocene or ferrocene; the ultrasonic dispersion time is 10 min to 50 min; and the stirring time is 2 h to 6 h.

6. The method for preparing the CMC-SiC composite material modified by liquid phase growth carbon nanotubes according to claim 5, characterized in that: In step 3, the CMC-SiC composite material body is a carbon cloth or a preform on which SiC is deposited; the vacuum impregnation time is 10 min to 60 min; In step 4, the heat treatment time is 1 h to 4 h.

7. The method for preparing the CMC-SiC composite material modified by liquid phase growth carbon nanotubes according to claim 6, characterized in that: In step 3, the preform is a carbon fiber preform or a SiC fiber preform; the structure of the preform is a two-dimensional laminate, a three-dimensional needle punching or a three-dimensional woven structure.

8. The method for preparing the CMC-SiC composite material modified by liquid phase growth carbon nanotubes according to claim 7, characterized in that: Step 1 is as follows: Phenolic resin powder and anhydrous ethanol were weighed separately, placed in a container and stirred until the phenolic resin powder was completely dissolved and the solution was clear and transparent, thereby preparing a phenolic resin solution with a mass fraction of 15%.

9. The method for preparing the CMC-SiC composite material modified by liquid phase growth carbon nanotubes according to claim 8, characterized in that: Step 2 is as follows: Weigh 5% of the mass of the phenolic resin powder with nickelocene, add it into the phenolic resin solution, disperse it by ultrasonic for 30 minutes, and continue stirring for 3 hours until the nickelocene is completely dissolved to obtain a mixed solution.

10. The method for preparing the CMC-SiC composite material modified by liquid phase growth carbon nanotubes according to claim 9, characterized in that: Step 3 specifically comprises immersing the carbon fiber preform with a three-dimensional woven structure prepared in advance in the mixed liquid and vacuum impregnating it for 30 minutes; Step 4 is specifically to take out the carbon fiber preform after vacuum impregnation and place it in a crucible, then put it into a tubular furnace, pass argon gas, and heat treat it at a heating temperature of 1000°C for 1.5 hours to obtain a carbon fiber preform modified by liquid phase growth carbon nanotubes.

Citation Information

Patent Citations

  • Carbon nanotube modified composite material and preparation method thereof

    CN115745643A

  • Continuous process for the production of carbon nanotube reinforced continuous fiber preforms and composites made therefrom

    WO2009110885A1